ANALISIS PENGARUH KUALITAS LAYANAN TERHADAP KEPUASAN DAN KEPERCAYAAN PASSANGER PT GARUDA INDONESIA (PERSERO) - Faizatul Fajariah (Valid: Jurnal Ilmiah, 2019)
This study aims to describe the effect of service quality toward satisfaction and confidence of passengers. This research is included in the explanatory research category. Sample in this research counted 99 people. The analytical technique uses path analysis. The main thing that can increase customer trust is the ability to interact. Quality of service can improve passenger satisfaction, which means that the better the quality of service provided by Garuda Indonesia Yogyakarta can increase passenger satisfaction. Quality of service can improve passenger's confidence, which means that the better quality of service provided by Garuda Indonesia Yogyakarta can improve passenger's confidence. Trust can increase passenger satisfaction, which means that increased confidence in passengers can improve passenger satisfaction. Trust can increase passenger satisfaction, which means that the higher the trust the passengers have, the higher the passenger's satisfaction level. Quality of service through empathy efforts that attention to customers more influential to create passenger confidence than on passenger satisfaction. Among the trust and satisfaction, satisfaction factors include suitability of expectations, interest in visiting again, willingness to recommend more precisely related to aspects of service at Garuda Indonesia Airlines Yogyakarta